Interdependence of building elements in the analysis of repair = Współzależność elementów budynku w analizie potrzeb remontowych - Nowogońska, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents a comparative analysis of the results of the evaluation of technical wear of residential buildings situated in Żary (a town in Lubuskie Voivodship) with the results of calculated percentage values of wear for the same buildings carried out with the use of time methods.
Keywords: zużycie techniczne budynków; ocena stanu technicznego; remonty; analiza potrzeb remontowych; współczynniki korelacji; technical wear of building; evaluation of technical wear; repairs; analysis needs repair